Evaluation of the Fuel Subsidy Removal Effect on the Performance of Cooperative Societies in Osogbo Local Goverment Area of Osun State - Taiwo Abdulahi (Saniya Institute, 2025)
This study evaluated the impact of removing the fuel subsidy on the performance of cooperative societies in the Osogbo Local Government Area of Osun State. 112 members of cooperative societies were selected using a multi-stage random sampling method. The results of the findings indicated that although the cooperatives provided diverse range of services, prevalent among them are: loans and savings mobilization, farm inputs supply, marketing and processing of agricultural produce, findings also revealed that the fuel subsidy removal had a moderate to high negative impact on the revenues and expenditures of cooperative societies in Osogbo LGA, which led to increased operational costs, declining revenues, reduced profitability, and the need to adjust pricing strategies and expenditures amongst others. Similarly, the removal of fuel subsidy had a moderate negative impact on the membership, assets, and service delivery of cooperative societies in Osogbo LGA, resulting in declining membership, challenges in attracting and retaining members, increased costs of maintaining and acquiring assets, and difficulties in providing quality services and accessibility. Thus, this led the cooperatives to adopt various strategies to cope with the effects of fuel subsidy removal, with moderate effectiveness. Several recommendations were proffered by the researcher, among which are that the government should consider implementing targeted support programs and incentives for cooperative societies, including access to affordable credit, subsidies for essential inputs and services.